Comparative study on Hylocereus polyrhizus peels extract and Aloe barbadensis leaves extract as potential natural-based sources in antibacterial and antioxidant activities / Nurul Amalina M. Z. and Hamidah J. S. - Md Fauzi, Nurul Amalina; Jaafar Sidek, Hamidah (Universiti Teknologi MARA, Perlis, 2019)
Aloe barbadensis leaves and Hylocereus polyrhizus are plants that are easily found in Malaysia. They are commonly studied for antibacterial activity and how they can benefit the human being. However it is not known about how the combination of both plants work to become the alternative way of remedies. The objectives of this study were to determine the antibacterial, antioxidant, and toxicity of Hylocereus polyrhizus peels and Aloe barbadensis leaves extracts. The antibacterial activities were evaluated towards the bacteria commonly associated with skin infections; which are Staphylococcus aureus, Propionibacterium acnes and Pseudomonas aeruginosa, using Kirby-Bauer Disc Diffusion method. The antioxidant activity was determined using DPPH assay. The toxicity activity was evaluated by exposing the extracts towards brine shrimp. As for the results, Aloe barbadensis extracts showed the highest antibacterial activity compared to Hylocereus polyrhizus and the combination of both extracts. For the antioxidant activity and the toxicity test, Hylocereus polyrhizus possessed the best result, where the IC50 obtained was 226.397 μg/ml and LC50 was 28588.76 μg/ml (non-toxic). In conclusion, Aloe barbadensis, Hylocereus polyrhizus and the combination of both have the potential to become alternative way as remedies instead of modern medicines.